The Rapid Growth of Coconut Estates in Indragiri Hilir 1980s – 1990s - Atqo Akmal; Warto Warto; Sariyatun Sariyatun (Jurnal Sejarah Citra Lekha, 2020)
Coconut estate is one of the vital agriculture sub-sectors in Indonesia because it has an important role in absorbing employment. In the early 20th century, Netherland Indies was one of the major copra exporters globally, and the eastern region of Nusantara contributed as the leading producer. However, in the 1930s – 1950s, the coconut-based economy's contraction phase in the eastern region had weakened the whole production. The Indonesian government tried to recover coconut estates and its economic market through several efforts, such as rehabilitating smallholder coconut estates, recovering copra trading, and starting coconut industrialization. Used historical research methods, this article described the shifting of Indonesia coconut-based economy from the past center of trade and production, in the eastern region of Indonesia, to a recent major producer and industry cluster in the Indragiri Hilir, Riau Province. In the 1980s – 1990s, the government efforts to improve coconut commodities have led to shifting the Indonesian coconut-based economy to Indragiri Hilir. Several policies issued by the government such as Smallholder Coconut Development Project, Proyek Peremajaan Rehabilitasi dan Perluasan Tanaman Ekspor (PRPTE), Nucleus Estate Smallholder (NES), Nucleus Estate Smallholder Transmigration (NES-Trans), and the local government funding, as well as the liberalization of coconut trading regulation, had stimulated rapid growth of coconut estates in Indragiri Hilir. Even though several schemes and governments attempt to develop smallholder coconut estates, the expansion rate was mostly dominated by self-funded smallholder coconut estates. During the 1980s – 1990s, the increasing demand for coconut from large-scale processing industries had attracted the smallholder to cultivate coconut.